Interagir à distance dans une communauté d’enseignants : effets sur les conceptions relatives au numérique et à l’enseignement de l’orthographe - Georges Ferone; Jacques Crinon (Recherches en Éducation)
Teacher communities have existed since the widespread use of the Internet, but three phenomena are now combined. These communities are developing strongly; they are explicitly claiming effects on the professional development of teachers and positioning themselves as a new actor in training; finally, they benefit from strong support from the Institution. To understand the effects of community participation on teachers’ pedagogical and didactic conceptions, we interviewed, by means of a questionnaire, members of the Twictée association, which aims to improve teaching and learning of spelling. Our results confirm other work. Participation in the Twictée network plays an important role in the emotional dimension; participation builds teachers’ confidence and enjoyment of teaching. On the other hand, they show more contrasting effects in the cognitive domain. Network members report more realistic conceptions of the benefits and barriers attributed to digital. On those of spelling and its teaching, we show that the Twictée network favours the circulation of notions borrowed from the field of spelling didactics, sometimes at the cost of a profound transformation of these notions.